Peanut oral immunotherapy modifies IgE and IgG4 responses to major peanut allergens - Vickery, Brian P.; Lin, Jing; Kulis, Michael; Fu, Zhiyan; Steele, Pamela H.; Jones, Stacie M.; Scurlock, Amy M.; Gimenez, Gustavo; Bardina, Ludmilla; Sampson, Hugh A.; Burks, A. Wesley (Journal of allergy and clinical immunology, 2013)
Patients with peanut allergy have highly stable pathologic antibody repertoires to the immunodominant B-cell epitopes of the major peanut allergens Ara h 1 to 3. We used a peptide microarray technique to analyze the effect of treatment with peanut oral immunotherapy (OIT) on such repertoires. Measurements of total peanut-specific IgE (psIgE) and peanut-specific IgG4 (psIgG4) were made with CAP-FEIA. We analyzed sera from 22 patients with OIT and 6 control subjects and measured serum specific IgE and IgG4 binding to epitopes of Ara h 1 to 3 using a high-throughput peptide microarray technique. Antibody affinity was measured by using a competitive peptide microarray, as previously described. At baseline, psIgE and psIgG4 diversity was similar between patients and control subjects, and there was broad variation in epitope recognition. After a median of 41 months of OIT, polyclonal psIgG4 levels increased from a median of 0.3 μg/mL (interquartile range [25% to 75%], 0.1-0.43 μg/mL) at baseline to 10.5 μg/mL (interquartile range [25% to 75%], 3.95-45.48 μg/mL; P < .0001) and included de novo specificities. psIgE levels were reduced from a median baseline of 85.45 kUA/L (23.05-101.0 kUA/L) to 7.75 kUA/L (2.58-30.55 kUA/L, P < .0001). Affinity was unaffected. Although the psIgE repertoire contracted in most OIT-treated patients, several subjects generated new IgE specificities, even as the total psIgE level decreased. Global epitope-specific shifts from IgE to IgG4 binding occurred, including at an informative epitope of Ara h 2. OIT differentially alters Ara h 1 to 3 binding patterns. These changes are variable between patients, are not observed in control subjects, and include a progressive polyclonal increase in IgG4 levels, with concurrent reduction in IgE amount and diversity.